(untitled) (Jurnal Komunikasi, 2018)
In today’s marketing era, consumers seem to have known about marketed products and no longer need explanation from a salesperson. The interaction between company and target consumers can be marketed through new media such as email, Facebook, WA, Instagram, and other forms. Such situations need to be in-depth researched in terms of whether personal selling contribution is still needed in marketing communication activities. Considering the uniqueness and personal selling advantages turns out that personal selling is an important partner that can not be replaced by other forms of marketing communications even if there is exposure to new media to promote products. The specialty of personal selling lies in its ability to interact directly to improvise the sales process through person to person communication. Dalam era pemasaran masa kini nampaknya konsumen dianggap sudah mengetahui tentang produk yang dipasarkan dan tidak memerlukan lagi penjelasan dari seorang wiraniaga. Interaksi perusahaan dengan pembeli sasaran dapat dilakukan melalui media baru seperti email, facebook, WA, instagram dan bentuk lainnya. Situasi demikianlah yang memerlukan kajian mendalam dalam kaitannya apakah kontribusi personal selling masih dibutuhkan dalam kegiatan komunikasi pemasaran. Memperhatikan keunikan dan kelebihan personal selling ternyata personal selling merupakan mitra penting yang tidak dapat tergantikan oleh bentuk komunikasi pemasaran lainnya sekalipun ada terpaan media baru untuk mempromosikan produk. Keistimewaan personal selling terletak pada kemampuan nya untuk berinteraksi secara langsung untuk mengimprovisasi proses penjualan melalui komunikasi person to person.